2019
DOI: 10.1155/2019/7602343
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activity against Streptococcus mutans of Individual and Mixtures of the Main Polyphenolic Compounds Found in Chilean Propolis

Abstract: Dental caries is multifactorial disease and an important health problem worldwide. Streptococcus mutans is considered as a major cariogenic agent in oral cavity. This bacteria can synthetize soluble and insoluble glucans from sucrose by glucosyltransferases enzymes and generate stable biofilm on the tooth surface. Biological properties of Chilean propolis have been described and it includes antimicrobial, antifungal, and antibiofilm activities. The main goal of this study was to quantify the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 34 publications
3
57
1
1
Order By: Relevance
“…Galangin significantly suppresses growth of vancomycin-intermediate Staphylococcus aureus (VISA) strain Mu50 [49]. Veloz et al [50] have shown that pinocembrin and apigenin are able to modify the architecture of S. mutans biofilm, reducing its thickness; antimicrobial activity against S. mutans has also been documented [50]. In our in vitro model, BLI-Pseudomonas exposure to propolis has been shown to reduce the levels of several phenolic compounds, as shown by a decrease in their corresponding peak areas; in particular, quercetin and CAPE are consistently affected, while pinobanksin-3-O-acetate and pinobanksin-3-O-butyrate appear to slightly decrease when compared to the control (propolis alone).…”
Section: Discussionmentioning
confidence: 99%
“…Galangin significantly suppresses growth of vancomycin-intermediate Staphylococcus aureus (VISA) strain Mu50 [49]. Veloz et al [50] have shown that pinocembrin and apigenin are able to modify the architecture of S. mutans biofilm, reducing its thickness; antimicrobial activity against S. mutans has also been documented [50]. In our in vitro model, BLI-Pseudomonas exposure to propolis has been shown to reduce the levels of several phenolic compounds, as shown by a decrease in their corresponding peak areas; in particular, quercetin and CAPE are consistently affected, while pinobanksin-3-O-acetate and pinobanksin-3-O-butyrate appear to slightly decrease when compared to the control (propolis alone).…”
Section: Discussionmentioning
confidence: 99%
“…The small aggregates containing two or three times more cells than the non-aggregated adherent units increase the bacterial number, whereas the big aggregates reduce the amount of adherent bacteria 9) . Apigenin had been shown to affect biofilm structure of S. mutans, resulting in a reduced thickness due to cellular aggregation 1) . In our study, apigenin showed significant effect on the aggregation rate as well as the biofilm structure.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries is an important health problem worldwide and highly related to biofilm formed by microorganisms in the oral cavity 1) . Oral biofilm comprises complex microorganisms, but Streptococcus mutans (S. mutans) is the major etiological microbe of dental caries in humans 2) .…”
Section: Introductionmentioning
confidence: 99%
“…Salivary pellicles composed of adsorbed macromolecular compounds delivered from saliva, blood, gingival fluids, bacteria, molecules and particles from the diet [95], Streptococcus mutans (S. mutans) and other oral bacteria adhere on the surface of enamel. All these substances and particles demineralize this surface resulting in the formation of dental caries [96][97][98]. To reduce the severity of such processes, gallic acid, present in various food and plants can inhibit the enamel demineralization as a calcium chelator and can enhance the remineralization of the demineralized enamel.…”
Section: Remineralization Cell Viability and Differentiationmentioning
confidence: 99%